PENGARUH LITERASI DIGITAL, LINGKUNGAN SEKOLAH, KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BISNIS DIGITAL DI SMKN 2 MOJOKERTO - Rohmatin, Ike; Sudarwanto , Tri (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
Vocational High Schools (SMK) play a strategic role in producing graduates who are competent and ready to enter the workforce, in line with the evolving demands of industry. However, at SMKN 2 Mojokerto, a number of students have not yet met the Minimum Mastery Criteria (KKM) in the Digital Business subject. The low learning outcomes are suspected to be related to limited digital literacy, the suboptimal role of the school environment in supporting the learning process, and the students’ low level of learning independence. This study aims to examine the influence of digital literacy, school environment, and learning independence on students' learning outcomes in the Digital Business subject at SMKN 2 Mojokerto. A quantitative approach with a causal associative design was employed. The population consisted of 137 eleventh-grade students, from which 103 were selected using purposive sampling. Data were collected through observation, documentation, and a Likert-scale questionnaire. Data analysis was performed using SPSS version 27. The findings revealed that digital literacy had a positive and significant effect on learning outcomes; the school environment had a negative and significant effect; while learning independence did not show a significant effect. Simultaneously, digital literacy, the school environment, and learning independence were found to have a significant influence on students’ learning outcomes.